2015
DOI: 10.4238/2015.october.5.10
|View full text |Cite
|
Sign up to set email alerts
|

Immunological characteristics of outer membrane protein omp31 of goat Brucella and its monoclonal antibody

Abstract: ABSTRACT. We examined the immunological characteristics of outer membrane protein omp31 of goat Brucella and its monoclonal antibody. Genomic DNA from the M5 strain of goat Brucella was amplified by polymerase chain reaction and cloned into the prokaryotic expression vector pGEX-4T-1. The expression and immunological characteristics of the fusion protein GST-omp31 were subjected to preliminary western blot detection with goat Brucella rabbit immune serum. The Brucella immunized BALB/c mouse serum was detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In addition, ribosomal protein L7/L12 functionally constitutes the 50S ribosome and plays an important role in controlling protein translational accuracy (Kirsebom and Isaksson, 1985). Based on previous reports, L7/L12, OMP22, OMP25 and OMP31 could stimulate strong immunity against Brucella infection (Goel and Bhatnagar, 2012; Zheng et al ., 2015; Du et al ., 2016; Minhas et al ., 2021). Therefore, in this study, a combination of four recombinant proteins L7/L12, OMP22, OMP25 and OMP31 can activate strong immune responses against Brucella infection in RAW 264.7 cells and BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ribosomal protein L7/L12 functionally constitutes the 50S ribosome and plays an important role in controlling protein translational accuracy (Kirsebom and Isaksson, 1985). Based on previous reports, L7/L12, OMP22, OMP25 and OMP31 could stimulate strong immunity against Brucella infection (Goel and Bhatnagar, 2012; Zheng et al ., 2015; Du et al ., 2016; Minhas et al ., 2021). Therefore, in this study, a combination of four recombinant proteins L7/L12, OMP22, OMP25 and OMP31 can activate strong immune responses against Brucella infection in RAW 264.7 cells and BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%
“…A subunit vaccine comprising BP26 triggers a mixed Th1/Th2 immune response in a mice model ( 7 ), and it has been also used in diagnosis of brucellosis ( 22 ). Animal experiments indicated that Omp31 can not only elicit a strong humoral immune response in mice, but also protects mice against Brucella infection ( 23 , 24 ). Omp2b is another important candidate for brucellosis diagnostics and vaccine research ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The OMPs detected by these antibodies were the proteins with a molecular weight of 25-27 kDa and 36-38 kDa (porin) (major proteins), and the proteins with a molecular weight of 10, 16.5, 19, 31-34, and 89 kDa (minor proteins). 26 The production of an mAb against OMPs with a molecular mass of 25-27 kDa (Ba-4, Ba-5), 36-38 kDa (Ba-6) of B. abortus S99 and rOMP31 of goat Brucella was performed by Farshad et al and Zheng et al 36,37 It was proven by Ghasemi et al that the immunized serum was achieved from a rabbit that was inoculated with attenuated B. melitensis. This serum contained antibodies against recombinant OMP31 (rOMP31).…”
Section: Discussionmentioning
confidence: 99%